2006
DOI: 10.2169/internalmedicine.45.1767
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Pheochromocytoma Presenting with Acute Abdomen and Pulmonary Edema

Abstract: F i g u r e 1 A. Ch e s t r a d i o g r a p h t a k e n a t t h e t i me o f a d mi ss i o n s h o we d d i f f u s e g r o u n d -g l a s s o p a c i t y o n b o t h l u n g s .F i g u r e 1 B . No n c o n t r a s t -e n h a n c e d CT s c a n s h o we d a r i g h t a d r e n a l ma s s wi t h r e t r o p e r i t o n e a l h e ma t o ma . * , r i g h t a d r en a l ma s s ; a r r o wh e a d s , r e t r o p e r i t o n e a l h e ma t o ma . (Fig. 1A). Abdominal computed tomography (CT) showed a hyper-enhancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In the literature, it has been found that emergency surgery without suitable BP checks and an incorrect preoperative diagnosis are strongly associated with a worse prognosis [3]. The death rate for the 54 cases in the literature was 34% [1,7]. Because the diagnosis was not made preoperatively, we could not give the patient α-adrenergic blockage therapy, instead, the patient was only given crystalloid fluid and erythrocyte suspension.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it has been found that emergency surgery without suitable BP checks and an incorrect preoperative diagnosis are strongly associated with a worse prognosis [3]. The death rate for the 54 cases in the literature was 34% [1,7]. Because the diagnosis was not made preoperatively, we could not give the patient α-adrenergic blockage therapy, instead, the patient was only given crystalloid fluid and erythrocyte suspension.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate was 31% for the 54 cases reported in the literature (9,10). The most important factor affecting the results of the surgery is the resuscitative treatment, which is done at the time of diagnosis and perioperatively (9).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of tumor rupture is unclear, TANAKA et al reported that rapid tumor growth or hemorrhage can increase the intratumoral pressure, which can subsequently cause not only tumor necrosis but also tumor rupture (2). There are several case reports showing a few CT or magnetic resonance imaging (MRI) figures, but none has described the imaging features in detail (2)(3)(4)(5). Moreover, most of these reports did not correlate the imaging and pathology features.…”
Section: Discussionmentioning
confidence: 99%
“…An adrenal hemorrhage is frequently associated with predisposing factors including trauma, sepsis, and coagulopathy (6)(7)(8). For these reasons, a spontaneous adrenal hemorrhage is extremely unusual and is sometimes observed in cases with a ruptured pheochromocytoma (1)(2)(3)(4)(5). A ruptured pheochromocytoma has frequently been reported to be a cyst-like tumor on CT or MRI, probably resulting from extensive cystic or necrotic changes (2,4,5).…”
Section: Discussionmentioning
confidence: 99%